Transformasi Digital Surat Kabar Harian Riau Pos Dalam Menghadapi Persaingan Global - Nurman, Muhammad Ali; Nasution, Belli; Yasir, Yasir (Peneliti.net, 2024)
The print media industry, especially newspapers, is experiencing severe shocks due to the rapid development of communication, information and digital technology. Riau Pos is the largest and oldest newspaper in Riau which has also felt the impact of technological disruption by experiencing a decline in circulation and income. To be relevant to current developments, Riau Pos implements digital transformation through various existing digital platforms. This research is intended to find out how the digital transformation of the Riau Pos Daily Newspaper as a traditional media is prepared to face global competition? The stages in this research are divided into three parts, namely (1) How is Riau Pos' strategy prepared in preparing for digital transformation to face global competition? (2) How is the transformation implemented by Riau Pos towards digital media facing global competition?This research uses descriptive qualitative research methods. Data was obtained by conducting in-depth interviews, observation and documentation. The research took as sources the Director who is also the Editor-in-Chief of Riau Pos, Deputy Editor-in-Chief, coverage coordinator and Riau Pos reporter. The results of this research show that Riau Pos has maintained its existence in the digital era by carrying out transformation using the mediamorphosis model. The model chosen focuses on developing new media in the form of websites and social media while still relying on the core business of newspapers. The two platforms, namely newspaper and digital, are managed side by side with a multiplatform concept so that they can reach a wider and more diverse audience. Riau Pos developed a digital business brand with Riau Pos Media. However, this development has not been followed by the creation of one application that can be used to access all service platforms owned by Riau Pos.